Hfq Regulates Efflux Pump Expression and Purine Metabolic Pathway to Increase Trimethoprim Resistance in Aeromonas veronii - Wang, Dan; Li, Hong; Ma, Xiang; Tang, Yanqiong; Tang, Hongqian; Huang, Dongyi; Lin, Min; Liu, Zhu (Frontiers in Microbiology, 2021)
Aeromonas veronii (A. veronii) is a zoonotic pathogen. It causes clinically a variety of diseases such as dysentery, bacteremia, and meningitis, and brings huge losses to aquaculture. A. veronii has been documented as a multiple antibiotic resistant bacterium. Hfq (host factor for RNA bacteriophage Qβ replication) participates in the regulations of the virulence, adhesion, and nitrogen fixation, effecting on the growth, metabolism synthesis and stress resistance in bacteria. The deletion of hfq gene in A. veronii showed more sensitivity to trimethoprim, accompanying by the upregulations of purine metabolic genes and downregulations of efflux pump genes by transcriptomic data analysis. Coherently, the complementation of efflux pump-related genes acrA and acrB recovered the trimethoprim resistance in Δhfq. Besides, the accumulations of adenosine and guanosine were increased in Δhfq in metabonomic data. The strain Δhfq conferred more sensitive to trimethoprim after appending 1 mM guanosine to M9 medium, while wild type was not altered. These results demonstrated that Hfq mediated trimethoprim resistance by elevating efflux pump expression and degrading adenosine, and guanosine metabolites. Collectively, Hfq is a potential target to tackle trimethoprim resistance in A. veronii infection.